Feeling in the Face of Uncertainty: Tacit Processes That Reveal Novel Learning - Kayrouz, David (Auckland University of Technology, 2025)
This study examines adults’ bodily felt sense within learning processes that enable personal and group transformations during unexpected encounters. Employing the extended epistemology of Heron and Reason’s (1997) ways of knowing, this study analyses the passage of six mature learners engaged in meaning making. As part of a co-operative inquiry the study uses artifacts for expression of a common experience while distinguishing between private and public domains of knowing. The qualities of knowing and knowledge pervading both private and public domains of perception are realised as tacit, implicit, and explicit forms of knowing-in-the-moment, guided by felt sense. The study’s findings indicate that, in the public domain, meaningfulness related to a critical felt sense that has been realised in the private domain underpins successful group and personal transformations with learning.